Sustainable shopping : consumer behavior in purchasing and donating secondhand clothes - Jönsson, Jenny; Wätthammar, Tina (SLU/Dept. of Economics, 2013)
Textiles are made in an unsustainable way and there is a need to find alternative ways and material to reduce the negative impacts on the environment, humans and animals. Problems like pollution, excessive water consumption and loss of soil fertility is a result of this lack of diversity. It is a necessity to find innovative alternatives in other fabrics due to the unsustainable use of cotton and polyester fibers. As in many other countries in the Western part of the world, in Sweden there is a rapid turnover and increased selling of clothes that result in increased textile waste. About 15 kilogram of textiles (net inflow) is consumed per person each year. Around three kilos of these 15 are either exported or given to charity. Consumers in Sweden throw away around half of the textiles bought per year and person.